The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1111/j.1475-6803.2004.00094.x
|View full text |Cite
|
Sign up to set email alerts
|

When‐issued Shares, Small Trades, and the Variance of Returns Around Stock Splits

Abstract: The increases in volatility after stock splits have long puzzled researchers. The usual suspects of discreteness and bid-ask spread do not provide a complete explanation. We provide new clues to solve this mystery by examining the trading of when-issued shares that are available before the split. When-issued trading permits noise traders to compete with a more homogenous set of traders, decreasing the volatility of the stock before the split. Following the split, these noise traders reunite in one market and v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
1

Year Published

2009
2009
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 20 publications
0
20
1
Order By: Relevance
“…On the empirical front, Lamoureux and Poon (1987), Schultz (2000) and Angel et al (2004) find an increase in institutional ownership following a split, while Ikenberry et al (1996) and Dennis and Strickland (2003) refute these findings. Examining the equity performance of firms executing stock splits, Fama et al (1969) and Byun and Rozeff (2003) found insignificant abnormal returns, which contradicts the results of Desai and Jain (1997) and Wu and Chan (1997).…”
Section: Introductioncontrasting
confidence: 45%
“…On the empirical front, Lamoureux and Poon (1987), Schultz (2000) and Angel et al (2004) find an increase in institutional ownership following a split, while Ikenberry et al (1996) and Dennis and Strickland (2003) refute these findings. Examining the equity performance of firms executing stock splits, Fama et al (1969) and Byun and Rozeff (2003) found insignificant abnormal returns, which contradicts the results of Desai and Jain (1997) and Wu and Chan (1997).…”
Section: Introductioncontrasting
confidence: 45%
“…Brooks and Chiou (1995) controlled for a variety of factors such as time of the transaction, and reported a premium of 0.75%. As further support of the inconvenience hypothesis, Angel, Brooks, and Mathew (2004) found that volume in the when-issued shares increases by three-fold following the record date of the stock split. Nayar and Rozeff (2001) argued and found evidence that the buyers' preference for when-issued shares versus unsplit shares near the record date leads to negative returns around that date.…”
Section: Literature Reviewmentioning
confidence: 81%
“…When-issued trading may also alleviate the inconveniences of trading in unsplit shares past the record date (Nayar and Rozeff 2001) or of receiving odd lot shares in the case of non-integer splits (Brooks and Chiou 1995). Angel et al (2004) point out that when-issued shares may attract small-volume traders; as such, they may increase liquidity in the market already before the effective split date.…”
Section: Related Literature On Stock Splits and When-issued Tradingmentioning
confidence: 97%